LEGAL CERTAINTY FOR BUILDINGS WITH BUILDING USE RIGHTS STANDS ON LAND WITH LAND MANAGEMENT RIGHTS - Santosa, Samuel Agung; Surya, M. Javana Krida; Muhammad, Maldi Omar; Humaerah, Nurul; Anugraha, Matius Hermawan (JURNAL DARMA AGUNG, 2024)
Land Management Rights (HPL) are the authority granted by the government to landowners to manage part of state land, as regulated in Article 2 Paragraph (4) of the Basic Agrarian Law. Generally, HPL is valid for 30 years so that the holder can utilize government land efficiently. However, there are still weaknesses in HPL regulations related to the legal consequences when Building Use Rights (HGB) are established on land that has HPL. This weakness has the potential to create legal uncertainty, such as the possibility of building removal or land rent increases that can be carried out by the landowner at any time. This condition can hinder investment in the property sector. Therefore, a revision is needed in the legislation that regulates both HGB and HPL to ensure legal clarity regarding buildings with HGB that are established on land managed using HPL. This research is expected to provide important contributions in the legal field and provide benefits to all parties involved, including HGB holders, landowners, and the government.